THE IMPACT OF THE FINANCIAL AND ECONOMIC CRISIS ON THE ACTIVITY OF UKRAINIAN RAILWAY TRANSPORT - Barash, Yu. S.; Korzhenevych, I. P.; Meliantsova, Yu. P.; Olinichenko, I. V. (Science and Transport Progress, 2009)
In the article an influence of the financial and economic crisis on the economy ofUkraineand the railway branch is analyzed.